Catalyst structures for oxygen reduction reactions, and fabrication method of the same
A catalyst structure with a Ti-O amorphous oxide layer and platinum promoter, manufactured via a novel process, addresses stability and cost issues in platinum-based catalysts, improving oxygen reduction reaction efficiency and stability.
Patent Information
- Application Number
- KR1020230149977
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-11-02
- Filing Date
- 2023-11-02
- Publication Date
- 2026-11-05
- Estimated Expiration
- 2043-11-02
AI Technical Summary
Existing platinum-based catalysts for oxygen reduction reactions in fuel cells suffer from poor long-term stability, high manufacturing costs, and complex processes, limiting their performance and scalability.
A catalyst structure comprising a catalyst material with a Ti-O amorphous oxide layer and a platinum promoter, manufactured through a method involving Ti powder, TiO2 powder mixing, sintering, melting, polishing, and cyclic electrophoresis to form a platinum nanocluster, enhancing electrochemical properties and stability.
The method improves the electrochemical catalytic properties, increases the surface area, and enhances the efficiency and long-term stability of the oxygen reduction reaction, reducing manufacturing time and costs while facilitating mass production.
Smart Images

Figure 112023121130007-PAT00003_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a catalyst structure for an oxygen reduction reaction and a method for manufacturing the same, and more specifically, to a catalyst structure comprising a catalyst material, an oxide layer on the surface of the catalyst material, and a platinum promoter on the oxide layer. Background Technology
[0002] One of the key factors determining the performance of a fuel cell is the oxygen reduction reaction (ORR) occurring at the air electrode, which is a reaction in which oxygen introduced from the outside meets electrons and is reduced. While mixtures of platinum and carbon are primarily used as commercial air electrode catalyst materials, the development of catalyst materials with higher performance and long-term stability is known to be a significant technological barrier.
[0003] Among these, research aimed at securing high performance is actively underway to develop various metal catalysts, focusing on the nanostructuring of platinum and the alloying of platinum with heterogeneous elements. While numerous materials have been developed that surpass the performance of platinum catalysts, long-term stability remains an unresolved technical challenge. In particular, it is widely known that the long-term stability of platinum catalyst materials used in the air electrodes of fuel cells, which generally operate at high temperatures, degrades due to bonding with oxygen atoms on the surface.
[0004] For example, Korean Patent Publication No. 10-2451629 discloses a method for manufacturing a platinum-based catalyst for an oxygen reduction reaction, comprising the steps of: pyrolyzing a platinum precursor solution containing an organic ligand to produce platinum-based nanoparticles; and heat-treating the platinum-based nanoparticles produced in the above step at 600 to 1200°C in an inert gas atmosphere with a hydrogen gas content of 1 to 20 v%, wherein the platinum-based nanoparticles are surrounded by a carbon shell having pores through which oxygen is permeable. The problem to be solved
[0005] The technical problem that the present invention aims to solve is to provide a method for manufacturing a catalyst structure with improved electrochemical catalytic properties.
[0006] Another technical problem that the present invention aims to solve is to provide a method for manufacturing a catalyst structure with an enhanced oxygen reduction reaction.
[0007] Another technical problem that the present invention aims to solve is to provide a catalyst structure with improved long-term stability for oxygen reduction reactions.
[0008] Another technical problem that the present invention aims to solve is to provide a method for manufacturing a catalyst structure with reduced manufacturing process costs.
[0009] Another technical problem that the present invention aims to solve is to provide a method for manufacturing a catalyst structure with reduced manufacturing time.
[0010] Another technical problem that the present invention aims to solve is to provide a method for manufacturing a catalyst structure that is easy to mass-produce.
[0011] The technical problems that the present invention aims to solve are not limited to those described above. means of solving the problem
[0012] To solve the above technical problem, the present invention provides a catalyst structure.
[0013] According to one embodiment, the catalyst structure comprises a catalyst material and a platinum promoter, wherein the catalyst material comprises at least one of a compound represented by the following <Chemical Formula 1>, a compound represented by the following <Chemical Formula 2>, or a compound represented by both <Chemical Formula 1> and <Chemical Formula 2>, and may comprise an oxide layer on the surface of the catalyst material and may comprise the platinum promoter on the oxide layer.
[0014] <Chemical Formula 1>
[0015] Ti2+x O(0≤x≤0.4)
[0016] <Chemical Formula 2>
[0017] Ti2O 1+y (0 <y≤0.4)
[0018] According to one embodiment, the platinum promoter may include a platinum nanocluster.
[0019] According to one embodiment, the work function of the platinum promoter may be lower than the intrinsic work function of platinum (Pt).
[0020] According to one embodiment, the oxide film may include a Ti-O amorphous compound layer.
[0021] According to one embodiment, the catalyst structure may include a powder or a bulk phase.
[0022] According to one embodiment, the bulk phase may include an ingot produced by a melt solidification method and a sintered product produced by a single crystal or sintering.
[0023] To solve the above technical problem, the present invention provides an oxygen reduction electrode to which the catalyst structure described above is applied.
[0024] According to one embodiment, the oxygen reduction electrode may include the catalyst structure described above.
[0025] To solve the above technical problem, the present invention provides a method for manufacturing the catalyst structure described above.
[0026] According to one embodiment, the method for manufacturing the catalyst structure comprises the steps of: preparing Ti powder, TiO2 powder, and a platinum promoter precursor; mixing the Ti powder and the TiO2 powder to produce a mixed powder; sintering the mixed powder to produce a catalyst material precursor; preparing a preliminary catalyst material by melting the catalyst material precursor; polishing the preliminary catalyst material to produce a catalyst material; and providing the platinum promoter precursor to the catalyst material and producing a platinum promoter on the catalyst material by cyclic electrophoresis. The catalyst material may include at least one of a compound represented by the following <Chemical Formula 1>, a compound represented by the following <Chemical Formula 2>, or a compound represented by both <Chemical Formula 1> and <Chemical Formula 2>.
[0027] <Chemical Formula 1>
[0028] Ti 2+x O(0≤x≤0.4)
[0029] <Chemical Formula 2>
[0030] Ti2O 1+y (0 <y≤0.4)
[0031] According to one embodiment, in the step of providing the platinum promoter precursor to the catalyst material and manufacturing the platinum promoter on the catalyst material by the cyclic aggregation method, the cyclic aggregation method may be performed repeatedly 100 times or more and 3,000 times or less.
[0032] According to one embodiment, the catalyst material may include an electronic material. Effects of the invention
[0033] A method for manufacturing a catalyst structure according to the present invention may include the steps of: preparing a Ti powder, a TiO2 powder, and a platinum promoter precursor; mixing the Ti powder and the TiO2 powder to produce a mixed powder; preparing a catalyst material precursor by sintering the mixed powder; preparing a pre-catalyst material by melting and solidifying the catalyst material precursor; polishing the pre-catalyst material to produce a catalyst material; and providing the platinum promoter precursor to the catalyst material and producing a platinum promoter on the catalyst material by cyclic electrophoresis.
[0034] In the step of providing the platinum promoter precursor to the catalyst material and manufacturing the platinum promoter on the catalyst material by the cyclic electrophoresis, the cyclic electrophoresis may be performed repeatedly at least 100 times and no more than 3,000 times. Accordingly, the platinum promoter (e.g., platinum nanocluster) can be easily formed on the catalyst material. As a result, the surface area of the catalyst structure is increased, thereby improving the electrochemical catalytic properties of the catalyst structure and improving the efficiency of the oxygen reduction reaction.
[0035] The catalyst structure manufactured by the above-described manufacturing method may comprise the catalyst material, an oxide film on the surface of the catalyst material, and a platinum promoter on the oxide film of the catalyst material.
[0036] The catalyst material of the catalyst structure may be a high-purity material with minimized impurities. Additionally, the oxide film on the surface of the catalyst material may include a Ti-O amorphous compound layer. Accordingly, the level of stabilization of the catalyst material may be improved. Furthermore, the surface area of the catalyst structure may be increased by the shape of the platinum promoter (e.g., platinum nanocluster) that substantially acts as a catalyst for the oxygen reduction reaction. Additionally, the work function of the platinum promoter may be lower than the intrinsic work function of platinum. Accordingly, oxygen adsorption on the catalyst structure may be prevented by the platinum promoter of the catalyst structure.
[0037] Accordingly, a catalyst structure with improved electrochemical catalytic properties, efficiency for oxygen reduction reactions, and long-term stability can be provided.
[0038] Accordingly, the above catalyst structure can be applied to an electrode for oxygen reduction. And, the above electrode for oxygen reduction can be applied to an oxygen reduction device. Brief explanation of the drawing
[0039] Figure 1 is a graph showing the analysis of a catalyst material according to Experimental Example 1 of the present invention by XRD. FIG. 2 is a graph for comparing the polarization curve of the oxygen reduction reaction (ORR) and the mass activity for the catalyst material according to Experimental Example 1 of the present invention, the catalyst structure according to Experimental Example 1, and the catalyst structure according to Comparative Example 1. FIG. 3 is a graph for comparing the long-term safety of the oxygen reduction reaction (ORR) for the catalyst structure according to Experimental Example 1 of the present invention, the catalyst structure according to Comparative Example 1, and the reference catalyst structure. Specific details for implementing the invention
[0040] Hereinafter, preferred embodiments of the present invention will be described in detail with reference to the attached drawings. However, the technical concept of the present invention is not limited to the embodiments described herein and may be embodied in other forms. Rather, the embodiments introduced herein are provided to ensure that the disclosed content is thorough and complete and to ensure that the concept of the present invention is sufficiently conveyed to those skilled in the art.
[0041] In this specification, when a component is described as being on another component, it means that it may be formed directly on the other component or that a third component may be interposed between them. Additionally, in the drawings, the thicknesses of the films and regions are exaggerated for the effective description of the technical content.
[0042] Additionally, although terms such as first, second, third, etc., have been used to describe various components in the various embodiments of this specification, these components should not be limited by such terms. These terms are used merely to distinguish one component from another. Accordingly, what is referred to as the first component in one embodiment may be referred to as the second component in another embodiment. Each embodiment described and illustrated herein also includes its complementary embodiment. Furthermore, in this specification, "and / or" is used to mean including at least one of the components listed before and after it.
[0043] In the specification, singular expressions include plural expressions unless the context clearly indicates otherwise. Furthermore, terms such as "include" or "have" are intended to specify the existence of the features, numbers, steps, components, or combinations thereof described in the specification, and should not be understood as excluding the existence or addition of one or more other features, numbers, steps, components, or combinations thereof. Additionally, in this specification, "connection" is used to include both indirectly connecting multiple components and directly connecting them.
[0044] In addition, in describing the present invention below, if it is determined that a detailed description of related known functions or configurations could unnecessarily obscure the essence of the invention, such detailed description will be omitted.
[0046] A method for manufacturing a catalyst structure according to an embodiment of the present invention may include the steps of: preparing a Ti powder, a TiO2 powder, and a platinum promoter precursor; mixing the Ti powder and the TiO2 powder to produce a mixed powder; preparing a catalyst material precursor by sintering the mixed powder; preparing a preliminary catalyst material by melting and solidifying the catalyst material precursor; preparing a catalyst material by polishing the preliminary catalyst material; and providing the platinum promoter precursor to the catalyst material and producing a platinum promoter on the catalyst material by cyclic electrophoresis.
[0047] In the step of preparing the mixed powder by mixing the above Ti powder and the above TiO2 powder, the above Ti powder and the above TiO2 powder may be mixed in an inert atmosphere to produce the above mixed powder in the form of a fillet. For example, the inert atmosphere may be an argon gas atmosphere. For example, the weight ratio of the above Ti powder and the above TiO2 powder may be 3:1. For example, the diameter of the fillet may be 1 cm. For example, the thickness of the fillet may be 3 mm to 5 mm.
[0048] In the step of preparing the catalyst material precursor by sintering the above-mentioned mixed powder, the mixed powder may be provided in a silica tube and sealed with a flame torch. For example, the flame torch may use oxygen or hydrogen. Then, the mixed powder sealed in the silica tube may be provided to a heat treatment furnace and sintered to produce the catalyst material precursor.
[0049] In the step of preparing the preliminary catalyst material by the melting and solidification method using the catalyst material precursor, the catalyst material precursor is loaded into a melting facility, and the melting and cooling processes are repeated in an inert and vacuum atmosphere to produce the preliminary catalyst material. For example, the melting facility may be an arc melting facility. For example, the inert atmosphere may be an argon gas atmosphere in which the catalyst material precursor can be melted by an arc. For example, the vacuum atmosphere may be 10 -5 It may be less than torr. For example, the melting and cooling processes may be repeated three or more times.
[0050] In the step of manufacturing the catalyst material by polishing the above-mentioned precatalytic material, the catalyst material can be manufactured by providing the precatalytic material to a polishing device and polishing the surface of the precatalytic material to make it flat.
[0051] Accordingly, the catalyst material may include at least one of the compounds represented by the following <Chemical Formula 1>, the following <Chemical Formula 2>, or the following <Chemical Formula 1> and the following <Chemical Formula 2>. For example, the catalyst material may include an electronic compound.
[0052] <Chemical Formula 1>
[0053] Ti 2+x O(0≤x≤0.4)
[0054] <Chemical Formula 2>
[0055] Ti2O 1+y (0 <y≤0.4)
[0056] Accordingly, impurities in the catalyst material can be minimized.
[0057] In contrast, if x in the above <Chemical Formula 1> exceeds 0.4, the impurity in the catalyst material may increase. For example, the impurity may be Ti metal. And, if y exceeds 0.4, the impurity in the catalyst material may increase. For example, the impurity may be TiO2.
[0058] Accordingly, according to an embodiment of the present application, the catalyst material may be prepared to include at least one compound among the compounds represented by <Chemical Formula 1>, <Chemical Formula 2>, or <Chemical Formula 1> and <Chemical Formula 2>. Accordingly, a high-purity catalyst material with minimized impurities within the catalyst material may be provided.
[0059] Additionally, an oxide film may be formed on the surface of the catalyst material. The oxide film may include a Ti-O amorphous compound layer. Accordingly, the platinum promoter described below can be easily formed on the catalyst material. As a result, the electrochemical catalytic properties of the catalyst structure described below are improved, and the efficiency of the oxygen reduction reaction can be enhanced.
[0060] In the step of providing the platinum promoter precursor to the catalyst material and manufacturing the platinum promoter on the catalyst material using the cyclic voltammetry method, specifically, the catalyst material is provided as the anode to a cyclic voltammetry system and a metal electrode is used as the cathode. The platinum promoter precursor is provided between the anode and the cathode, and the platinum promoter can be manufactured on the upper surface of the anode using the cyclic voltammetry method. For example, the platinum promoter may be in the form of a nanocluster. As another example, the platinum promoter may be in various particle forms such as spherical, plate-shaped, or linear. For example, the size unit of the platinum promoter may be from nm to um. Additionally, a metal layer may be formed on the lower surface of the upper anode facing the upper surface. Accordingly, the contact resistance of the anode may be reduced.
[0061] In the step of providing the platinum promoter precursor to the catalyst material and manufacturing the platinum promoter on the catalyst material by the cyclic aggregation method, the cyclic aggregation method may be repeated 100 to 3,000 times. Accordingly, the platinum promoter can be easily manufactured on the upper surface of the anode. As a result, the electrochemical catalytic properties of the catalyst structure are improved, and the efficiency of the oxygen reduction reaction can be improved.
[0062] In contrast, if the above-mentioned cyclic aggregation method is repeated less than 100 times, the platinum promoter may not be formed on the catalyst material. As a result, the electrochemical catalytic properties of the catalyst structure are reduced, and the efficiency of the oxygen reduction reaction may be reduced.
[0063] In addition, if the above-mentioned cyclic aggregation method is repeated more than 3,000 times, the platinum promoter on the catalyst material may be formed in the form of a film rather than a nano-cluster or particle. As a result, the electrochemical catalytic properties of the catalyst structure may be reduced, and the efficiency of the oxygen reduction reaction may be reduced.
[0064] Accordingly, in the step of providing the platinum promoter precursor to the catalyst material according to the embodiment of the present application and manufacturing the platinum promoter on the catalyst material by the cyclic aggregation method, the cyclic aggregation method may be performed repeatedly at least 100 times and no more than 3,000 times. Accordingly, the platinum promoter in the form of a nano-cluster or a particle can be easily formed on the catalyst material. As a result, the electrochemical catalytic properties of the catalyst structure are improved, and the efficiency of the oxygen reduction reaction can be improved.
[0065] As another example, a platinum promoter can be manufactured on the catalyst material by providing the catalyst material to the platinum promoter precursor to which heat is provided and depositing the platinum promoter on the surface of the catalyst material.
[0066] In conclusion, the method for manufacturing the catalyst structure according to an embodiment of the present application may include the steps of: preparing the Ti powder, the TiO2 powder, and the platinum promoter precursor; mixing the Ti powder and the TiO2 powder to produce the mixed powder; producing the catalyst material precursor by sintering the mixed powder; producing the preliminary catalyst material by melting the catalyst material precursor; polishing the preliminary catalyst material to produce the catalyst material; and providing the platinum promoter precursor to the catalyst material and producing the platinum promoter on the catalyst material by circulating current.
[0067] In the step of providing the platinum promoter precursor to the catalyst material and manufacturing the platinum promoter on the catalyst material by the cyclic electrophoresis, the cyclic electrophoresis may be performed repeatedly at least 100 times and no more than 3,000 times. Accordingly, the platinum promoter can be easily formed on the catalyst material. As a result, the electrochemical catalytic properties of the catalyst structure are improved, and the efficiency of the oxygen reduction reaction can be improved.
[0068] Accordingly, the manufactured catalyst structure may comprise the catalyst material, the oxide film on the surface of the catalyst material, and the platinum promoter on the oxide film of the catalyst material. Furthermore, the catalyst structure may be in at least one form among powder or bulk. For example, if the catalyst structure is in bulk, the catalyst structure may be an ingot manufactured by melt solidification, and a single crystal or a sintered product manufactured by sintering.
[0069] In addition, the catalyst material of the catalyst structure may include at least one of the compounds represented by the following <Chemical Formula 1>, the following <Chemical Formula 2>, or the following <Chemical Formula 1> and the following <Chemical Formula 2>. For example, the catalyst material may include an electronic compound.
[0070] <Chemical Formula 1>
[0071] Ti 2+x O(0≤x≤0.4)
[0072] <Chemical Formula 2>
[0073] Ti2O 1+y (0 <y≤0.4)
[0074] Accordingly, the catalyst material of the catalyst structure may be a high-purity material with minimized impurities within it. Additionally, the surface of the catalyst material may include the oxide film. The oxide film may include the Ti-O amorphous compound layer. Accordingly, the level of stabilization of the catalyst material may be improved. Furthermore, the platinum promoter, which substantially performs the role of a catalyst, may be, for example, a platinum nanocluster or a platinum particle. Accordingly, the surface area of the catalyst structure may be increased. Also, the work function of the platinum promoter may be lower than the intrinsic work function of platinum. Accordingly, oxygen adsorption on the catalyst structure may be prevented by the platinum promoter of the catalyst structure.
[0075] Accordingly, the electrochemical catalytic properties of the catalyst structure can be improved. As a result, the efficiency and long-term stability of the oxygen reduction reaction can be improved.
[0076] In conclusion, the catalyst structure according to the embodiment of the present application may comprise the catalyst material, the oxide film on the surface of the catalyst material, and the platinum promoter on the oxide film of the catalyst material. Furthermore, the catalyst structure may be in at least one form among powder or bulk.
[0077] The catalyst material of the catalyst structure may be a high-purity material in which impurities within the catalyst material are minimized. Furthermore, the oxide film on the surface of the catalyst material may include a Ti-O amorphous compound layer. Accordingly, the level of stabilization of the catalyst material may be improved. Additionally, the surface area of the catalyst structure may be increased by the shape of the platinum promoter, which substantially acts as a catalyst for the oxygen reduction reaction. Moreover, the work function of the platinum promoter may be lower than the intrinsic work function of platinum. Accordingly, oxygen adsorption on the catalyst structure may be prevented by the platinum promoter of the catalyst structure.
[0078] Accordingly, a catalyst structure with improved electrochemical catalytic properties, efficiency for oxygen reduction reactions, and long-term stability can be provided.
[0079] Accordingly, the above catalyst structure can be applied to an electrode for oxygen reduction. And, the above oxygen reduction electrode can be applied to an oxygen reduction device.
[0080] The oxygen reduction device may include an oxygen reduction electrode, a metal electrode spaced apart from the oxygen reduction electrode and serving as a counter electrode to the oxygen reduction electrode, and an electrolyte disposed between the reduction electrode and the counter electrode. When a voltage is applied to the oxygen reduction device, the reduction of oxygen gas can be easily achieved by the catalyst structure of the oxygen reduction electrode. For example, the counter electrode may be in various forms such as a wire, mesh, or coil. For example, the electrolyte may include an acid electrolyte or an ionized liquid.
[0082] Hereinafter, specific experimental examples and characteristic evaluation results of the catalyst material and catalyst structure according to the embodiments of the present invention are described.
[0084] Catalytic material according to Experimental Example 1
[0085] In a Glove Box under an inert atmosphere (argon gas), Ti powder and TiO2 powder were mixed in a weight ratio of 3:1 to produce a mixed powder in the form of pellets (diameter 1 cm, thickness 3 mm to 5 mm).
[0086] Then, the above mixed powder was vacuum-sealed in a silica tube, provided to a furnace, and sintered to produce a catalyst material precursor.
[0087] Then, the catalyst material precursor was provided to an arc melting facility chamber, and after forming a vacuum atmosphere, an inert gas such as argon was provided at a level capable of driving an arc. Subsequently, an arc was applied to melt and cool the catalyst material precursor (performed at least three times) to produce a preliminary catalyst material.
[0088] Then, the surface of the above-mentioned preliminary catalyst material was polished using a polishing device to produce a catalyst material.
[0090] Catalytic material according to Experimental Example 1-2
[0091] A catalyst material was prepared in the same manner as in Experimental Example 1, except that Ti powder and TiO2 powder were mixed in a weight ratio of 3.8:1 to prepare a mixed powder in the form of fillets.
[0093] Catalytic material according to Experimental Example 1-3
[0094] A catalyst material was prepared in the same manner as in Experimental Example 1, except that Ti powder and TiO2 powder were mixed in a weight ratio of 3.1:0.9 to prepare a mixed powder in the form of fillets.
[0096] Catalyst structure according to Experimental Example 1
[0097] A catalyst material according to Experimental Example 1 was provided as the anode in a circulating current system, a metal electrode was used as the cathode, a solution containing Pt as a platinum promoter precursor was provided between the anode and the cathode, and a voltage sweep was performed using a circulating current method to form a platinum promoter (Pt) on the catalyst material, thereby producing a catalyst structure.
[0099] Catalyst structure according to Comparative Example 1
[0100] A commercially available Pt / C (Pt 20wt%) was prepared as a catalyst structure.
[0102] Figure 1 is a graph showing the analysis of a catalyst material according to Experimental Example 1 of the present invention by XRD.
[0103] Referring to Figure 1, the catalyst material according to Experimental Example 1 was analyzed by XRD Rietveld refinement.
[0104] As can be seen in Fig. 1, the catalyst material according to Experimental Example 1 is [Ti2O] 2+ㆍ 2e - It can be seen that it is electronic cargo containing
[0106] FIG. 2 is a graph for comparing the polarization curve of the oxygen reduction reaction (ORR) and the mass activity for the catalyst material according to Experimental Example 1 of the present invention, the catalyst structure according to Experimental Example 1, and the catalyst structure according to Comparative Example 1.
[0107] Referring to FIG. 2(a), after exposing the catalyst material (Ti2O) according to Experimental Example 1, the catalyst structure (Pt / Ti2O) according to Experimental Example 1, and the catalyst structure according to Comparative Example 1 (Pt / C) to air, linear sweep voltammetry (LSV) was measured for the catalyst material (Ti2O) according to Experimental Example 1, the catalyst structure (Pt / Ti2O) according to Experimental Example 1, and the catalyst structure according to Comparative Example 1 (Pt / C). Referring to FIG. 2(b), mass activity was measured for the catalyst structure (Pt / Ti2O) according to Experimental Example 1 and the catalyst structure according to Comparative Example 1 (Pt / C).
[0108] As can be seen in FIG. 2(a), when comparing the measurement results of the catalyst material according to Experimental Example 1 and the catalyst structure according to Experimental Example 1, the catalyst structure according to Experimental Example 1 has a limiting current density and half-wave potential (E 1 / 2 It can be seen that ) is high. Therefore, it can be seen that the method of providing a platinum promoter on a catalyst material according to the embodiment of the present application is a method of improving the electrochemical catalytic properties of a catalyst structure.
[0109] And, when comparing the measurement results of the catalyst structure according to Experimental Example 1 and the catalyst structure according to Comparative Example 1, it can be seen that the limiting current density of the catalyst structure according to Experimental Example 1 and the catalyst structure according to Comparative Example 1 are at a similar level.
[0110] As can be seen in FIG. 2(b), the catalyst structure according to Experimental Example 1 has a higher mass activity in the range of 0.4V to 0.9V than the catalyst structure according to Comparative Example 1. Therefore, it can be seen that the method of providing a platinum promoter on a catalyst material according to the embodiment of the present application is a method for improving the electrochemical catalytic properties of a catalyst structure.
[0112] FIG. 3 is a graph for comparing the long-term safety of the oxygen reduction reaction (ORR) for the catalyst structure according to Experimental Example 1 of the present invention, the catalyst structure according to Comparative Example 1, and the reference catalyst structure.
[0113] Referring to Fig. 3, for the catalyst structure according to Experimental Example 1 (Pt / TiO2), the catalyst structure according to Comparative Example 1 (Commercial Pt / C), and the reference catalyst structure (Porous Fe-NC, N-doped graphene nanoribbon / CNT, Pt / Fe-NC), the long-term stability for ORR was evaluated by measuring the current density under conditions in which a 0.1M KOH solution was provided at room temperature and an overpotential of 0.4V was applied for 350 hours.
[0114] As can be seen in FIG. 3, the long-term stability (95%) of the catalyst structure according to Experimental Example 1 is significantly superior to that of the catalyst structure according to Comparative Example 1 and the reference catalyst structures.
[0115] It is interpreted that this is due to the fact that, as the catalytic material of the catalyst structure according to the embodiment of the present invention is an electron, electrons of the catalytic material are transferred to the platinum promoter, and the work function of the platinum promoter becomes lower than the intrinsic work function of platinum. Accordingly, it can be seen that the adsorption of oxygen on the catalyst structure is prevented by the platinum promoter of the catalyst structure, thereby improving the long-term stability of the catalyst structure.
[0117] Although the present invention has been described in detail using preferred embodiments, the scope of the invention is not limited to specific embodiments and should be interpreted by the appended claims. Furthermore, those skilled in the art will understand that many modifications and variations are possible without departing from the scope of the invention.
Claims
Claim 1 A catalyst structure for an oxygen reduction reaction comprising a catalytic material and a platinum promoter, wherein the catalytic material comprises at least one of a compound represented by the following <Chemical Formula 1>, a compound represented by the following <Chemical Formula 2>, or a compound represented by both <Chemical Formula 1> and <Chemical Formula 2>, the catalytic material comprises an oxide layer on its surface, and the platinum promoter comprises the platinum promoter on the oxide layer. <Chemical Formula 1>Ti 2+x O(0≤x≤0.4)<Chemical Formula 2>Ti2O 1+y (0 <y≤0.4) Claim 2 A catalyst structure for an oxygen reduction reaction comprising, in claim 1, a platinum promoter being a platinum nanocluster. Claim 3 A catalyst structure for an oxygen reduction reaction according to claim 1, wherein the work function of the platinum promoter is lower than the intrinsic work function of platinum (Pt). Claim 4 In claim 1, the oxide layer comprises a Ti-O amorphous compound layer, forming a catalyst structure for an oxygen reduction reaction. Claim 5 A catalyst structure for an oxygen reduction reaction comprising a powder or bulk form in claim 1. Claim 6 In claim 5, the bulk phase comprises any one of an ingot or single crystal produced by a melt solidification method, or a sintered product produced by sintering, forming a catalyst structure for an oxygen reduction reaction. Claim 7 An electrode for oxygen reduction comprising the catalyst structure according to claim 1. Claim 8 A method for manufacturing a catalyst structure for an oxygen reduction reaction comprising the steps of: preparing Ti powder, TiO2 powder, and a platinum promoter precursor; mixing the Ti powder and the TiO2 powder to produce a mixed powder; producing a catalyst material precursor by sintering the mixed powder; producing a preliminary catalyst material by melting and solidifying the catalyst material precursor; polishing the preliminary catalyst material to produce a catalyst material; and providing the platinum promoter precursor to the catalyst material and producing a platinum promoter on the catalyst material by cyclic electrophoresis, wherein the catalyst material comprises at least one of a compound represented by the following <Chemical Formula 1>, a compound represented by the following <Chemical Formula 2>, or a compound represented by both <Chemical Formula 1> and <Chemical Formula 2>. <Chemical Formula 1> Ti 2+x O(0≤x≤0.4)<Chemical Formula 2>Ti2O 1+y (0 <y≤0.4) Claim 9 A method for manufacturing a catalyst structure for an oxygen reduction reaction according to claim 8, comprising the step of providing the platinum promoter precursor to the catalyst material and manufacturing the platinum promoter on the catalyst material by the cyclic electrophoresis, wherein the cyclic electrophoresis is performed repeatedly 100 times or more and 3,000 times or less. Claim 10 In claim 8, the catalyst material is a method for manufacturing a catalyst structure for an oxygen reduction reaction comprising an electron cargo.
Citation Information
Patent Citations
Active particle-containing catalyst, method for producing same, electrode including said catalyst, and battery including said electrode
JP5907736B2
Method for producing titanium suboxide particles and titanium suboxide particles
JP6994684B2
